(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Female reproductive health is highly sensitive to hormonal and environmental factors, and diet is a significant modifiable factor influencing reproductive outcomes. This study aimed to investigate the impact of high-salt diets on the weight and size of the uterus and ovaries in female albino Wistar rats. Forty-four (44) female albino Wistar rats weighing between 200 and 250 g were randomly assigned to four groups comprising 11 albino Wistar rats each. The designated control group was fed with a non-high salt diet ad libitum; the other groups were fed 2.5 %, 3.5 %, and 4.5 % NaCl diets, respectively. All albino Wistar rats in groups 2, 3, and 4 were fed the experimental diet for 6 weeks. The male albino Wistar rats were housed separately before mating and allowed access to rat chow and water. The study showed that a high salt diet resulted in a significant decrease in the weight of the ovaries, the weight of the uterus and the fertility index. These findings show the importance of dietary regulation in preserving reproductive function and mitigating the adverse effects of metabolic disturbances. Thus, a high salt diet could be detrimental to the female reproductive system.